(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: Micronized purified flavonoid fractions (MPFF) have been used extensively throughout Europe and Asia to treat hemorrhoidal disease for at least two decades. MPFF decreases venous stasis by improving venous tone and lymphatic outflow and suppressing the local inflammatory response. Objective: To compare mean pain score and recurrence in patients on micronized purified (Daflon) versus placebo in the management of post-hemorrhoidectomy pain. Methods: A randomized controlled trial was conducted in Jinnah Postgraduate Medical Center, Karachi from September 2010 to March 2016. 3536 Patients were randomly allocated into two groups by drawing sealed opaque envelopes by a third person not related to the study, from a box containing equal paper slips bearing group A and group B, just before going to the operating room. Out of 3536 patients, 1768 were allocated to Group A (Daflon), and 1768 to Group B (Placebo). At the end of 5-year follow-up, recurrence was observed in 14.3% of Daflon patients and 26.7% of placebo patients (p = 0.01). Group A took Daflon 500mg, whereas Group B took a placebo. Two tablets of Daflon 500mg were given every 8 hours and 12 hours (6 tablets per day, i.e., 3000 mg/day for the first 4 days and then 2000mg for the next 3 days) from the first postoperative day up to the 7th postoperative day (POD) and then 1 tablet of daflon 500mg was given every 12 hours for the next 4 weeks in daflon group in addition to paracetamol and a similar inert tablet resembling Teflon. Patients were advised to measure pain on a daily basis till the seventh postoperative day. The outcome of pain was measured at the first follow-up on 7th POD and 21st POD and the mean pain score was calculated. The patient is followed up on 6 monthly basis for the next 5 years to check for the recurrence Results The mean age of the patient in the control group was 40 ± 10.28 years and the mean age of the patients in the DAFLON group was 37.5 ± 9.0 years. The mean weight of the patients in the control group was 50 ± 1.91 Kg and the mean weight of the patients in the DAFLON group was 51.9 ± 2.69 Kg. The mean pain score in the control group was 4 ± 2.43 and the mean pain score in the DAFLON group was 2.19 ± 1.84.